A Case Report of Recurrent Covid-19 Infection of a Physician in Bangladesh: Re-infection or Persistence Infection? (Bangladesh Journal of Infectious Diseases, 2020)
The novel coronavirus disease (COVID-19) has created a large problem to the healthcare system all over the world. “Retest Positive” for SARS‐CoV‐2 from “recovered” patients (COVID‐19) has been reported recently which raised several questions for the COVID‐19 disease. In this case report, we had described a patient who became positive after 1 month from the initial infection with SARS-CoV-2. It is therefore possible that recurrences should be actually persistent infections in which PCR resulted falsely negative during initial infection when he left home isolation assuming himself disease free. The discharge criteria should be ensured for a recovered patient to prevent the relapse or persistence of COVID-19.Bangladesh Journal of Infectious Diseases, October 2020;7(suppl_2):S57-S60